A 51 ka sedimentary sequence in a seamount basin, Eastern Arabian Sea: Records for paleoceanographic and paleoclimate conditions. (1st April 2022) - Neelavannan, Kannaiyan; Hussain, Shaik Mohammad; Sangode, Satish J.; Prakasam, Muthusamy; Sen, Indra Sekhar; Veerasingam, Subramanian; Tyagi, Abhishek; Kumar, Pankaj; Singh, Pramod
Graphical abstract: Highlights: Mineral magnetic parameters reveal the state of ocean ventilation and anoxia during the last 51 ka. The MIS 3 monsoonal intensity regulated changes in detrital influx in the EAS. Enhanced ocean-reducing conditions were reported during the Heinrich and deglaciation periods. Abstract: A 5.4 m thick sediment core at ∼ 517 m water depth from a seamount basin off the Goa coast in the Eastern Arabian Sea (EAS) is examined for the mineral magnetic, carbonate and organic carbon variability. The 51 ka BP dated record is represented by Marine Isotope Stages (MIS) 3 to 1 under varying rates of sedimentation from 1.9 to 5.2 cm/ka. Comparison with records from adjacent cores for OC, TN, and CaCO3, this study indicates strong coupling of the seamount basin sedimentation with paleo-oceanographic conditions governed by southwest (SW) monsoon. The mineral magnetic parameters assigned three zones of variable paleo-oceanographic-paleoclimatic conditions marked by the interplay of high coercivity (oxidative) and low coercivity (reducing) mineralogy, that can be attributed to various factors including ocean ventilation governed by bottom water inflow of oxygen-depleted Sub-Antarctic Mode Waters and Antarctic Intermediate Water flows (SAMW-AAIW). This study emphasizes the significance of seamount basins as faithful recorders of long-term thermocline changes along with strong coupling to paleoceanographic conditions.